Bacterial peritonitis in paediatric appendicitis; microbial epidemiology and antimicrobial management - Keir Bhaskar; Simon Clarke; Luke S. P. Moore; Stephen Hughes (BMC, 2023)
Abstract Background Appendicitis remains a common surgical emergency in children. Empirical antibacterial treatment is indicated to reduce infective complications. We investigate the bacterial pathogens identified intra-operatively during appendectomies in children to guide empirical surgical antimicrobial prophylaxis options. Methods A retrospective analysis of patients (< 18 years old) undergoing an appendectomy across a multisite London hospital (Nov 2019-March 2022) was undertaken. Patient-related outcomes including length of hospital stay (LOS), days of antibacterial therapy (DOT), intra-operative microbiology and post-operative radiology reports were interrogated. Results 304 patients underwent an appendectomy during this period; 39.1% of patients had intraoperative samples cultured. Bacterial pathogens were found in 73/119 (61.3%) cases; the most common isolates being Escherichia coli (42.0%), Pseudomonas aeruginosa (21.0%), milleri Streptococcus spp. (14.3%) and Bacteroides fragilis (5.9%). Polymicrobial infection was common (32/73). Isolation of Pseudomonas spp. from intra-operative sampling was associated with a greater LOS (7.0 vs. 5.0 days; p = 0.011) but nil effect on the incidence of postoperative collections. Presence of milleri Streptococcus spp. was associated with longer LOS (7.0 vs. 5.0 day; p = 0.007), DOT (12.0 vs. 8.5 day; p = 0.007) but had no observed outcome on postoperative collections (29.4% vs. 18.6%; p = 0.330). 48% of E. coli positive cultures were co-amoxiclav resistant and prolonged LOS compared to the non-resistant group (7.0 vs. 5.0 days; p = 0.040) but had no difference in post-operative collections (29.2% vs. 17.9%; p = 0.260). Conclusion A high proportion of children with appendicitis have Pseudomonas spp. isolated, leading to a prolonged LOS. Evolving Enterobacterales resistance and the presence of Pseudomonas spp. necessitate extended antibacterial coverage for paediatric appendectomies with evidence of peritonitis.